2022
DOI: 10.1146/annurev-biophys-111821-072110
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanics of Blood Clot and Thrombus Formation

Abstract: Mechanical properties have been extensively studied in pure elastic or viscous materials; however, most biomaterials possess both physical properties in a viscoelastic component. How the biomechanics of a fibrin clot is related to its composition and the microenvironment where it is formed is not yet fully understood. This review gives an outline of the building mechanisms for blood clot mechanical properties and how they relate to clot function. The formation of a blood clot in health conditions or the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 148 publications
(178 reference statements)
0
6
0
Order By: Relevance
“…The relationship between thrombotic disorders and clot mechanical properties has been consistently demonstrated. 3,6,[34][35][36][37] For example, studies have reported lower stiffness of in vitro clots of patients with bleeding conditions, whereas higher stiffness was observed in clots made from plasma of patients in thrombotic states. 3,36 Furthermore, plasma clots express unexpectedly low toughness for a ductile material 38 and are less resilient to rupture than other biological hydrogels, such as collagen, cartilage, and others, despite being extremely deformable.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between thrombotic disorders and clot mechanical properties has been consistently demonstrated. 3,6,[34][35][36][37] For example, studies have reported lower stiffness of in vitro clots of patients with bleeding conditions, whereas higher stiffness was observed in clots made from plasma of patients in thrombotic states. 3,36 Furthermore, plasma clots express unexpectedly low toughness for a ductile material 38 and are less resilient to rupture than other biological hydrogels, such as collagen, cartilage, and others, despite being extremely deformable.…”
Section: Discussionmentioning
confidence: 99%
“…This result was credible since good stability and resistance to enzymatic cleavage and shear forces have been demonstrated for fully coagulated BCC. [21][22][23] Therefore, centrifugation performed after BCC formation resulted in a slight impact on leukocyte distribution. The lowest DNA yield was 12.30 μg/g BCC in one upper segment with a leukocyte concentration of 5.27 × 10 6 cells/mL, meaning that adequate DNA for further application could be obtained even with 0.25 g BCC.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies should be performed to dissect the role of autophagy in hemostasis-osteogenesis interplay, a recently identified vital part of bone regeneration. It is noteworthy that research on blood clots has gradually emerged in the field of bone regeneration, especially in terms of the kinetics of the contribution of fibrin, tissue factor, and platelets [ 176 ]. Consequently, future studies may need to focus on the relationship between autophagy and the structure/function of clots, whether an interaction between autophagy and the progress of inflammation or the function of cells or platelets, which affect the differences in the structure of thrombi and kinetics of formation as a consequence of bone injury.…”
Section: Therapeutic Approaches For Bone Diseases By Modulating Autop...mentioning
confidence: 99%